Dietary approaches to stop hypertension diet and obesity: A cross-sectional study of Iranian children and adolescents - Sahar Golpour-Hamedani; Noushin Mohammadifard; Alireza Khosravi; Awat Feizi; Sayyed Morteza Safavi (ARYA Atherosclerosis, 2017)
BACKGROUND: Few studies have investigated the effects of dietary approaches to stop hypertension (DASH) diet on obesity in children. The present study was conducted to examine adherence to the DASH diet in relation to obesity in children and adolescents, Isfahan, Iran. METHODS: A cross-sectional study was carried out among 456 children aged 11-18 years who were selected by random cluster sampling method. Dietary intakes were assessed using a validated Food Frequency Questionnaire (FFQ). The DASH score was constructed based on food items emphasized or minimized in the DASH diet. Anthropometric measurements were conducted based on standard protocols. General and abdominal obesity were defined based on body mass index ≥ 95th percentiles and waist: height ratio of more than 0.5, respectively. RESULTS: Higher adherence to DASH diet was inversely associated with general obesity (odds ratioT1 vs. T3 3.34, 95% confidence interval 1.28-8.75); however, after controlling for confounding factors, this association disappeared. Furthermore, higher adherence to DASH diet was negatively associated with central obesity in children, but the relation was not statistically significant. CONCLUSION: We concluded that there was an inverse nonsignificant association between adherence to DASH diet and general obesity indices after adjustment for potential confounders. Further, well-designed randomized clinical trial studies are suggested to find out the effect of DASH diet on obesity obviously.